The demand for central clearing: To clear or not to clear, that is the question - Mario Bellia; Giulio Girardi; Roberto Calogero Panzica; Loriana Pelizzon; Tuomo Peltonen (Leibniz Institute for Financial Research SAFE, 2022)
This paper empirically analyses whether post-global financial crisis regulatory reforms have created appropriate incentives to voluntarily centrally clear the over-the-counter (OTC) derivative contracts. We use confidential European trade repository data on single-name sovereign credit default swap (CDS) transactions and show that both the seller and the buyer manage counterparty exposures and capital costs, strategically choosing to clear when the counterparty is riskier. The clearing incentives seem particularly responsive to seller credit risk, which is in line with the notion that counterparty credit risk (CCR) is asymmetric in CDS contracts. The riskiness of the underlying reference entity also enters the decision to clear as it affects both CCR capital charges for OTC contracts and central counterparty clearing house (CCP) margins for cleared contracts. Lastly, we find evidence that when a transaction helps netting positions with the CCP and hence lower margins, the likelihood of clearing is higher.
Keywords: G18; G28; G32; 330; Credit Default Swap (CDS); Central Counterparty Clearing House (CCP); European Market Infrastructure Regulation (EMIR); Sovereign CDS